On the dynamics of ozone depletion events at Villum Research Station in the High Arctic - J. B. Pernov; J. B. Pernov; J. B. Pernov; J. L. Hjorth; L. L. Sørensen; H. Skov (Atmospheric Chemistry and Physics)
Ozone depletion events (ODEs) occur every spring in the Arctic and have implications for the region's atmospheric oxidizing capacity, radiative balance, and mercury oxidation. Here, we comprehensively analyze ozone, ODEs, and their connection to meteorological and air mass history variables through statistical analyses, back trajectories, and machine learning (ML) at Villum Research Station, Station Nord, Greenland, from 1996 to 2019.